Effects of increasing crystalline amino acids and the subsequent change in diet net energy on growing pig performance - Steidinger, M.U.; Usry, J.L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Three individual trials were conducted to evaluate the effect of increasing the amount of crystalline amino acids (L-lysine, L threonine, and DL-methionine) as a replacement for soybean meal in the diet on pig growth performance. A second objective was to determine if increasing net energy (NE) concentration in the diet as a result of increased crystalline amino acids and less soybean meal would affect pig growth. In all three studies, pigs (each approximately 21 lb) were fed a cornsoybean meal diet, or diets with 2, 4, 6, or 8 lb/ton L-lysine HCl and other amino acids to maintain their proper ratio relative to lysine. In Experiments 1 and 3, added fat level was constant at 1%. In Experiment 2, the fat level was reduced slightly as amino acids replaced soybean meal to account for the slight change in ME as synthetic amino acids were added to the diet. In Experiment 1, increasing L-lysine and other crystalline amino acids had no effect on ADG, but F/G improved (linear, P<0.05). In Experiment 2, ADG tended (linear, P<0.09) to increase and F/G improved (quadratic, P<0.04) with increasing L-lysine. In Experiment 3, ADG and ADFI tended (P<0.09) to increase with increasing L-lysine HCl, but F/G was unchanged. In summary, these results indicate that in the young pig, up to 8 lb of Llysine HCl with other amino acids to maintain a proper ratio relative to lysine are effective replacements for soybean meal in the diet. Furthermore, when replacing soybean meal with crystalline amino acids, feed efficiency improvements are correlated with changes in the diet’s net energy concentration. Using ME to calculate the energy value of low-protein amino acid fortified diets will tend to underestimate the diet's actual energy value.
Keywords: Pigs; Growth; Net energy; Amino acids; Swine